2013
DOI: 10.1016/j.jacc.2012.07.072
|View full text |Cite
|
Sign up to set email alerts
|

Novel Predictors of Left Ventricular Reverse Remodeling in Individuals With Recent-Onset Dilated Cardiomyopathy

Abstract: Both CMR and serial BNP testing provide a better prediction of LVRR in recent-onset DCM than EMB results, other biomarkers, and the conventional methods of follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
113
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(127 citation statements)
references
References 28 publications
11
113
3
Order By: Relevance
“…158,159 In addition, it has recently been shown that low levels of BNP are predictive of recovery of left ventricular function in patients with heart failure. 150,160 In patients with heart failure, increases in MR-proANP and copeptin are associated with an increased risk of death or transplantation although the effect of copeptin does not seem to be independent of other biomarkers and clinical parameters.…”
Section: Natriuretic Peptidesmentioning
confidence: 99%
“…158,159 In addition, it has recently been shown that low levels of BNP are predictive of recovery of left ventricular function in patients with heart failure. 150,160 In patients with heart failure, increases in MR-proANP and copeptin are associated with an increased risk of death or transplantation although the effect of copeptin does not seem to be independent of other biomarkers and clinical parameters.…”
Section: Natriuretic Peptidesmentioning
confidence: 99%
“…Our findings are in line with those of 2 recent CMR studies that have investigated the capacity of LGE in predicting LV remodeling in patients with recent-onset nonischemic cardiomyopathy. In a study including 44 patients, Kubanek et al 11 demonstrated that a lower extent of LGE at baseline CMR was an independent predictor of LV-RR at 12 months. However, in this study, one third of patients had increased troponin at study entry, and endomyocardial biopsy revealed myocardial inflammation and genomes of cardiotropic viruses in 34% and 66% of patients, respectively, indicating an inflammatory or viral cause of LV dysfunction in a sizeable number of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies reported that late gadolinium enhancement (LGE) detected by cardiovascular magnetic resonance (CMR) may be a useful marker for predicting LV-RR in patients with nonischemic cardiomyopathy. 10,11 However, these studies had a…”
mentioning
confidence: 99%
“…We often had difficulty defining the disease duration and found a statistical overlap between this parameter and having familial cardiomyopathy. Important predictors such as brain natriuretic peptide and magnetic resonance imaging, 28 as well as genetic analysis, were not available in the majority of patients, and thus could not be analyzed.…”
Section: Discussionmentioning
confidence: 99%